The Effectiveness of Telling Method Assisted with Flannel Apron to Improve Social Skills of Early Childhood Children - Mudayanah, Mudayanah; Budiartati, Emmy; Mulawarman, Mulawarman (Journal of Primary Education, 2021)
The social skills of children already exist since they are born. Thus, they should obtain stimulation at their early age so they can maximally develop. It is because social skills are important for every individual to create interaction with their environments. This research aims to test the effectiveness of the telling method assisted with flannel apron toward the early childhood children's social skills. This research applied the experimental method with a pretest-posttest control group design. The data collection techniques were observation sheets and social skills. The sampling technique was purposive sampling because the researchers took the sample with certain considerations from a population. The data analyses were Mann-Whitney and Wilcoxon hypothetic tests. The tests showed that the method assisted with a flannel apron could effectively improve the learners' learning outcomes. The hypothetic tests showed that the applied method significantly influenced the social skill improvement of children aged 5-6 years old with a p lesser than 0.05. It was obtained from the mean score of the children's social skills after being treated. They got the category of excellently appropriately developed (BSB). The hypothetic test also showed a p-value lesser than 0.05. It proved the effectiveness of the telling method assisted with a flannel apron to improve social skills of the early childhood.